Detection of a single transverse crack in a CFRP cross-ply laminate by visualizing mode conversion of Lamb waves. (1st March 2022) - Yu, Fengming; Saito, Osamu; Okabe, Yoji
Abstract: Detection of transverse crack (TC) is important in establishing reliable structural health monitoring (SHM) and nondestructive inspection (NDI) for warning the potential occurrence of large-scale damage in carbon fiber reinforced plastic (CFRP) structures at an earlier stage. In this research, a diagnostic method that is sensitive to a single TC was established by visualizing laser-induced guided ultrasonic waves in a cross-ply CFRP laminate. First, the phenomenon of TC-induced mode conversion in the laminate was clarified using finite element analysis (FEA) of harmonic oscillations. This FEA method is explicit and precise for investigating the conversion behavior of individual modes in a cracked plate. Then, the conversion phenomenon was also validated by another FEA-based pulse laser ultrasonic simulation. Finally, to observe the mode conversion phenomenon in practice, we conducted an experiment with a laser ultrasonic visualizing inspector (LUVI). The LUVI system could visualize the wave propagation in a two-dimensional (2D) wavefield that was formed on the surface of the CFRP cross-ply laminate with a single TC. By observing the image results of wave propagation, we verified that the wave component of the A0 mode was converted from the S0 mode at a TC even though the converted A0 mode had a much smaller amplitude than the incident S0 mode in the cross-ply CFRP laminate. Thus, those visualization results could be used to detect a single TC in the CFRP cross-ply laminate reliably.